2009
DOI: 10.1073/pnas.0908617106
|View full text |Cite
|
Sign up to set email alerts
|

Native state dynamics drive the unfolding of the SH3 domain of PI3 kinase at high denaturant concentration

Abstract: Little is known about the role of protein dynamics in directing protein unfolding along a specific pathway and about the role played by chemical denaturants in modulating the dynamics and the initiation of unfolding. In this study, deuterium-hydrogen exchange (HX) detected by electrospray ionization mass spectrometry (ESI-MS) was used to study the unfolding of the SH3 domain of the PI3 kinase. Unfolding on the principal unfolding pathway occurs in 2 steps, both in the absence and in the presence of 1.8 M guani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 38 publications
(58 reference statements)
6
62
0
Order By: Relevance
“…In these conditions, the unfolding reaction occurs in multiple steps. 55 Importantly, the final unfolding of an intermediate to the fully unfolded state does not occur in an all-ornone manner. These conditions are identical with the strongly stabilizing folding conditions utilized in that study, so the initial stage of refolding would be expected to be the reverse of the last stage of unfolding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these conditions, the unfolding reaction occurs in multiple steps. 55 Importantly, the final unfolding of an intermediate to the fully unfolded state does not occur in an all-ornone manner. These conditions are identical with the strongly stabilizing folding conditions utilized in that study, so the initial stage of refolding would be expected to be the reverse of the last stage of unfolding.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a partially folded intermediate, which forms at a late stage during the folding of the PI3K SH3 domain, has been identified. 54 Studies of the unfolding of the PI3K SH3 domain, using hydrogen exchange detected by mass spectrometry, 55 in the absence and in low concentrations of denaturant also suggested that the dissolution of structure during unfolding occurs in many steps; hence, refolding too must occur in many steps in the absence and in low concentrations of denaturant. Nevertheless, earlier refolding studies were not able to detect any intermediate on the refolding pathway, probably because a suitable high-resolution probe was not used.…”
Section: Introductionmentioning
confidence: 99%
“…43 It should be noted that the bimodal isotope distribution patterns observed in three fragments of the aggregates are not attributable to uncorrelated HDX occurring in local structural regions in aggregate molecules under the quench conditions (pH 2.5, 4°C), because such patterns are not observed for the same three fragments derived from native moPrP or deuterated moPrP that were also subjected to exactly the same quench conditions as were the aggregates (Fig. 5).…”
Section: Conformational Heterogeneity Increases As Oligomers Convert mentioning
confidence: 91%
“…8,9 It has been postulated, 10,11 and has also been experimentally shown for many proteins, [12][13][14] 16 or by mutagenesis of the protein sequence [17][18][19] or by using a more sensitive detection method to probe the folding reaction. [20][21][22] Identifying and populating intermediate states during folding and unfolding, 23 as well as subsequent characterization of their kinetic role, 24 remain a major goal in protein folding studies. Deamidation of glutamyl and asparaginyl residues is an important nonenzymatic post-translational modification of proteins and peptides.…”
Section: Introductionmentioning
confidence: 99%